Pengaruh Latihan Variasi Terhadap Peningkatan Kemampuan Passing Dalam Permainan UKM Futsal Puteri UNIMUDA Sorong - Mesalina Rumaropen, Persila; Harmaman; Anwar, Saiful (Jurnal Muara Olahraga, 2024)
This research aims to determine the effect of triangle training on passing in UKM Futsal Unimuda Sorong futsal players. The method used is experimental. The results of research and hypothesis testing prove that the average difference in futsal passing ability scores for students before being given constant passing training was 7.2, whereas after being given constant passing training the passing ability score was 9.6, resulting in an increase. Based on the results of hypothesis testing, it proves that the average difference in the value of students' futsal passing ability before being given the changed passing training was 7.8, whereas after being given the changing passing training the value of the students' futsal passing ability was 9.8, resulting in an increase. From the calculated t statistic for training and passing, it remains = 21.81 using a significance level of 5% from d.b = (N-1) = 15 – 1 = 14, the table value = 2.262. From the statistical calculations, tcount for passing practice changes = 15 using a significance level of 5% from d.b=(N-1)=15–1=14, the table value = 2.262. This means that the calculated t value is greater than t table or 15 > 2.262 or the increase between pre-test and post-test is 15 with a mean deviation of 2 with a percentage increase of 25.64%